Purification and properties of beta-lactamase from Bacteroides fragilis. - Britz, M L (1978)
Beta-Lactamase activity was detected either biologically or using the chromogenic cephalosporin 87/312 in 20 clinical isolates of Bacteroides fragilis with penicillin G minimal inhibitory concentrations of 10 to 100 micrograms/ml. Strain AM78 (minimal inhibitory concentration, greater than 1,000 micrograms/ml) was used to optimize the conditions for production, assay, and storage of the enzyme. The enzymes are cell associated, with less than 1% of activity being found in culture fluids during growth, and can be released from the cell surface by modified osmotic shock procedure. This procedure causes concomitant release of cyclic phosphodiesterase activity. Substrate profiles and the effects of inhibitors were determined for enzymes partially purified by osmotic shock release and gel filtration. The enzymes are cephalosporinases with some penicillinase activity and are inhibited by p-chloromercuribenzoate, cloxacillin, and carbenicillin. The molecular weight, as determined by gel filtration, is 29,000 to 31,000. A method for the purification of the beta-lactamase from strain AM78 is described: the specific activity of the purified enzyme was 3,424 U/mg, about 3,000-fold that of the crude, cell-associated enzyme.